SIMULATION MODELING OF OUTBOUND LOGISTICS OF SUPPLY CHAIN: A CASE STUDY OF TELECOM COMPANY - Jayant, Arvind; Gupta, pardeep; Garg, Suresh; Wadhwa, Subhash (International Journal of Industrial Engineering: Theory, Applications and Practice, 2012)
<span style="font-family: ";Times New Roman";,";serif";; font-size: 10pt; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-size: 12.0pt; mso-bidi-font-style: italic; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The present work has been done for a telecom company <span style="font-family: ";Times New Roman";,";serif";; font-size: 10pt; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-size: 12.0pt; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">with a focus on cost and flexibility in effectively deals with changing scenario. In this paper, the major problems faced by company at upper end of supply chain and sales outlet are analyzed and a complete inventory analysis on one of a company product is done by developing an Inventory model for the company bound store/distribution center and optimal inventory policy is suggested for the outbound logistics on the basis of simulation analysis. This model is flexible enough to respond to the market fluctuations more efficiently and effectively. The model is developed in Microsoft EXCEL. <span style="font-family: ";Times New Roman";,";serif";; font-size: 10pt; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-size: 12.0pt; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> Significance: Increasing competitive pressures and market globalization are forcing the firms to develop supply chains that can quickly respond to customer needs. The inventory model for the company’s bound store/outbound logistics has been developed & simulated to reduce the operating cost, stock out, to make supply chain agile. Key words: Supply Chain, Outbound Logistics, Information Technology, Simulation, Operating Cost, Inventory.